STUDI EKSPLORATIF TENTANG KONSEP DIRI DAN PERILAKU KOPING PADA INDIVIDU DENGAN CEREBRAL PALSY - , Siti Maimunah; , Supra Wimbarti, Ph.D. ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Several previous studies showed that most individuals with cerebral palsy showed a negative self-concept. The aim of the present study was to determine and examine more deeply how the self-concept and coping behavior in individuals with cerebral palsy. Research informants obtained by using a purposive technique which is the characteristics specified in advance. The characteristics of the informants used are: Individuals with cerebral palsy, mental retardation is not accompanied and not accompanied by other disabilities. Data collection techniques used in this study are in-depth interviews, observation and use of documentation that can be used as additional information required. These results indicate that almost all infomant have unclear self-concept (self ambiguous concept). The most dominant factor in affecting their self-concept is a physical disability and feedback from the environment. In the selection of coping strategies, almost all infromant use problem-focused coping. The form of coping behavior conducted by informants, among others, are trying to relax or are not burdened with the physical condition and felt normal like everyone else. Source of the most widely used coping is positive beliefs and social support. Researchers also found that self-concept of individuals with cerebral palsy is not related to the severity but is strongly influenced by external factors. Another interesting research findings was the discovery of typical in almost all the informants are they always have a "gratitude" for their life even though they are have physical limitations due to cerebral palsy. These conditions are very unique and special that will be difficult to find in other countries.